The Influence of Cocopeat Plant Media and Manure on the Growth of Ketapang (Terminalia cattapa L.) in Telaga Cemara Beach Forest, Holmafen Village, Muara Tor District, Sarmi Regency - Isobela Kornelia Felle; Alfred Alfonso Antoh; Edoward Krisson Raunsay; Maik N R Akobiarek; Leonard Elisa Aisoi; David Reinhard Jesajas (Postgraduate, University of Mataram, 2023)
Planting media with a certain composition and different treatments influence the growth of a plant. This research was carried out for 5 months from December 2022 -May 2023 with the aim of research to find out the right composition for planting T. catappa plants in the rehabilitation process of the Telaga Cemara beach forest in Holmafen Village, Muara Tor District, Sarmi Regency. The composition of the growing media used in this study was manure, cocopeat, and soil. The research design used was Completely Randomized Design (CRD). There are three variables used in this study, namely the independent variable (combination of Cocopeat manure and soil), dependent variable (type of tree planted), and control variable (soil without treatment). The results showed that there was an effect of treatment on the Ketapang plant which showed significant results on the five parameters tested, NL (T2K3), LL (T2K1), LW (T2K1), PH (T2K1), NB (T2K1). Based on the results of linear regression, the correct composition was obtained, namely the composition of 32.5% cocopeat, manure 17.5%, and land 50%. Â Â